CO2 fluxes from organic soils in Sweden 2012-2016 - Grelle, Achim (Swedish University of Agricultural Sciences, 2019)
CO2 fluxes from a cultivated and a set-aside agricultural filed on organic soils in Harbo, Sweden, between 2012 and 2016, measured by eddy-covariance.

For full details, see publication:
Hadden, D. & Grelle, A (2017). The impact of cultivation on CO2 and CH4 fluxes over organic soils in Sweden, Agricultural and Forest Meteorology, 243, 15 September, 1-8. DOI: 10.1016/j.agrformet.2017.05.002

Koldioxidflöden från odlade och obrukade mark i Harbo, Sverige, mellan 2012 och 2016, uppmätta med eddy-kovarians.

För fullständiga detaljer, se publikationen:
Hadden, D. & Grelle, A (2017). The impact of cultivation on CO2 and CH4 fluxes over organic soils in Sweden, Agricultural and Forest Meteorology, 243, 15 September, 1-8. DOI: 10.1016/j.agrformet.2017.05.002
Koldioxidflöden från organiska jordar i Sverige 2012-2016
Keywords: SOIL RESPIRATION; ecosystem process; soil biota; Land use; Markanvändning; Soil; Mark; Environmental Sciences; Miljövetenskap; Microbiology; Mikrobiologi; Biota; Biologi och ekologi; Environment; Miljö